Cytokine Expression in the Colonic Mucosa of Human Immunodeficiency Virus-Infected Individuals before and during 9 Months of Antiretroviral Therapy - Schulbin, Hubert (American Society for Microbiology (ASM), 2008)
High-level human immunodeficiency virus (HIV) replication and the rapid breakdown of the mucosal immune system are the hallmarks of HIV infection in the gut. Cytokine dysregulation may be related to both phenomena. Using real-time PCR we quantified the colonic mucosal mRNA expression of selected proinflammatory and regulatory (gamma interferon [IFN-gamma], tumor necrosis factor alpha [TNF-α], and interleukin-2 [IL-2], IL-4, IL-6, and IL-10) and HIV-inhibitory (IL-16, CCL3, and CCL5) cytokines for 10 HIV-infected patients before and during 9 months of highly active antiretroviral therapy (HAART). HIV RNA and T-cell dynamics were measured in the colonic mucosa and the blood. Seven HIV-negative individuals served as controls. The mucosal mRNA expression of TNF-α, IFN-gamma, IL-4, IL-6, and IL-10 was significantly higher in HIV-infected patients than in control patients and remained elevated during 9 months of HAART despite the decline in blood and mucosal HIV RNA levels and an increase in the level of CD4(+) T lymphocytes. The mRNA levels of CCL3 and CCL5, both of which were elevated before treatment, returned to nearly normal during therapy. Despite reductions in levels of mucosal HIV RNA and the restoration of mucosal CD4(+) T lymphocytes, antiretroviral therapy failed to restore the normal colonic immunologic environment.